The effectiveness of a counseling program based on positive thinking skills to reduce the alienation on a sample of anonymous descendant in the orphanage in Riyadh - Al-Zahrani, Sara Ayed; Al-Amri, Ali Saeed (Journal of Educational and Psychological Sciences, 2023)
The current study aimed to identify the effectiveness of a counseling program based on positive thinking skills in reducing alienation among anonymous descendant in the orphanage in Riyadh, the sample of the study consisted of 22 orphan females that are located in the Residential care home in Riyadh, they were distributed into two groups; an experimental group and a control group with 11 for each. To achieve the goal of the study, the researcher used the Alienation Scale based on Seeman's point of view prepared by (Punia, 2017), and the researcher has Arabized it. The researcher also prepared a counseling program based on positive thinking skills to reduce alienation among the study sample by using Quasi-experimental Design. The findings of the study showed that there were statistically significant differences at the significance level (α = 0.01) between the scores of the experimental group and the control group in the Post-measurement in favor of the experimental group, and there were statistically significant differences at the significance level (α = 0.01) between the scores of the experimental group’s degrees in the two measurements the pre and post measurement in favor of the post measurement, and there were no statistically significant differences between the scores of the control group in the pre and post measurements, and there were no statistically significant differences between the scores of the experimental group in the pre and post measurements. The study recommended spreading awareness about orphans through influential people and preparing campaigns in cooperation with orphans to prove their effectiveness in society as others, and to show the opinion of religion about the unknown parents, and research in the areas of developing and building positive thinking skills and cognitive processes on orphans who have been exposed to additional shocks.
Keywords: alienation; positive thinking; unknown parentage